Diabetic Foot Ulcers: Impact on Quality of Life and Instruments for Its Measurement - Khairunisa Qomariyanti; Rani Sauriasari; Ratu Ayu Dewi Sartika (Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Diabetic foot ulcers are one of the complications of diabetes mellitus, which have a negative impact on quality of life due to the risk of infection and amputation. Pharmacists can measure quality of life to see the success of therapy and monitor the effectiveness of the drugs. One way to measure quality of life is to use instruments. There are general instruments and disease-specific instruments. This review explores various overarching theories about diabetic foot ulcers, their impact on quality of life, and their measurement instruments.